Europski sustav osposobljavanja osoba za vozače vozila na motorni pogon i mjesto Republike Hrvatske u tom sustavu - Zuber, Nenad; Smoljan, Ivan (Promet - Traffic&Transportation, 2012)
The analytical data on the status of road traffic safety inthe Republic ofCroatia in 1995 as compared to the year1994indicates a slight decrease in the number of injuries and fatalinjuries sustained in road traffic accidents, in the incidence ofaccidents with injuries and incidence of accidents in general,despite the reported increase in motor fuel sales and active integrationof a substantial segment of the road system in the Republicof Croatia.Regardless of the causes of road traffic accidents, relevantfactors of influence, types of road traffic accidents, locations,vehicle structure and technical functioning status, and circumstancesof accidents, it is indisputable that the years of servicei.e. experience (or better, non-experience) of drivers appear tobe of major impact upon the number of accidents. Of 62,120road traffic accidents in 1994, 44.4% of accidents resultingfrom driver error were caused by drivers having up to threeyears of driving experience, making 42.9% of all accidents.This fact is both logical and notorious, applying not only tothe Republic of Croatia but to most European countries. Themethods and activities taken to change these figures (effecttheir decrease) differ.